2019
DOI: 10.1039/c8an01895b
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework-based fluorescent sensing of tetracycline-type antibiotics applicable to environmental and food analysis

Abstract: With the use of a masking agent, a luminescent MOF realized the selective fluorescent sensing of tetracyclines over many other kinds of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…The extraction of tetracyclines from fish muscle was conducted with acetonitrile by a simple solid liquid extraction (SLE) procedure. In fish, pork and milk samples recoveries ranged between 96.35% and 102.57%, while the LODs were found between 0.28 nM-0.30 nM [45].…”
Section: Detection Of Antibiotics In Seafood and Fish Samplesmentioning
confidence: 95%
See 3 more Smart Citations
“…The extraction of tetracyclines from fish muscle was conducted with acetonitrile by a simple solid liquid extraction (SLE) procedure. In fish, pork and milk samples recoveries ranged between 96.35% and 102.57%, while the LODs were found between 0.28 nM-0.30 nM [45].…”
Section: Detection Of Antibiotics In Seafood and Fish Samplesmentioning
confidence: 95%
“…Except for the use of MOFs as extraction sorbents enhancing the extraction step of antibiotics, these novel materials have been used in recent years as a novel kind of fluorescent sensing materials. Liu et al constructed a MOF-based sensing system which had specific response to tetracyclines TC (tetracycline, chlortetracycline and oxytetracycline) antibiotics [45]. The novel luminescent MOF material (In-sbdc) was synthesized by mixing indium (III) chloride (InCl3) and 4,4'-stilbene-dicarboxylic acid (H2sbdc) in DMF-H2O at room temperature.…”
Section: Detection Of Antibiotics In Seafood and Fish Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Liu et al [173] reported the in-sbdc MOF with strong and stable emission in water for tetracycline type antibiotics analysis in environment and food. Chlortetracycline (CTC) and oxytetracycline (OTC) were chosen on behalf of tetracycline type antibiotics due to their extensive application.…”
Section: Antibiotic Detectionmentioning
confidence: 99%